2019
DOI: 10.1039/c9sc03417j
|View full text |Cite
|
Sign up to set email alerts
|

Freeze the dynamicity: charge transfer complexation assisted control over the reaction pathway

Abstract: Aqueous CT complexes of donor and acceptor molecules with reactive thiol groups were frozen and lyophilized to get alternate D–A assemblies in the solid state. Oxidation of the thiols resulted in asymmetric disulfides exclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The understanding of the supramolecular processes involved in the peptide assemblies also opened up the possibility of creating new generation of smart soft-materials with wide range of applications ( Figure 1 ) ( Ahmed et al, 2017 ; Lampel et al, 2018 ; Tian et al, 2018 ; Singha et al, 2019a ; Singha et al, 2019b ; Dasgupta and Das, 2019 ; Tarvirdipour et al, 2020 ). Amongst different types of applications of peptide hydrogels, their use in biomedical or therapeutic purposes holds the major share( Chen and Zou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the supramolecular processes involved in the peptide assemblies also opened up the possibility of creating new generation of smart soft-materials with wide range of applications ( Figure 1 ) ( Ahmed et al, 2017 ; Lampel et al, 2018 ; Tian et al, 2018 ; Singha et al, 2019a ; Singha et al, 2019b ; Dasgupta and Das, 2019 ; Tarvirdipour et al, 2020 ). Amongst different types of applications of peptide hydrogels, their use in biomedical or therapeutic purposes holds the major share( Chen and Zou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that copper can act as a catalyst in oxidation reaction in polymer, which can accelerate the generation of perhydrates as following procedure 3,32 . As discussed above, 1024 shown the best anti-oxidation effect in the presence of copper in comparison with 3110 and 1010 for LDPE, which was attributed to the metal-ligand interactions between hydrazide group and copper ions to prevent the further oxidation of materials 10,33 . Therefore, computation simulation was used to confirm the existence of complex.…”
Section: Resultsmentioning
confidence: 88%
“…Recently, we have shown the effect of molecular arrangement of two thiol molecules (in the aggregated state) on the disulfide formation possibility. 15 It was found that the thiol groups need to be in a very close proximity (∼4 Å) in order to form the disulfide bonds. Following our previous report, energy minimized structures for two molecules of the same peptides are obtained using DFT calculation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Short peptide based self-assembled systems are receiving significant current interest as biomaterials, mainly because of their biocompatibility and degradability. These smart soft materials have found applications in various fields, including drug delivery, , matrix for cell proliferation, , protective storage of proteins, sensors, , nanofabrication, organic methodology, , and organic electronics, to name a few. One of the most common outcomes of the self-assembly of these short peptides is the formation of hydrogels. , According to need, with proper permutation and combination of the constituent amino acids, the properties of these hydrogels can be altered.…”
Section: Introductionmentioning
confidence: 99%